Perkembangan Populasi Nematoda Puru Akar (Meloidogyne spp.) dan Tingkat Kerusakan Pada Beberapa Tanaman Familia Solanaceae - KHOTIMAH, NURUL; WIJAYA, I NYOMAN; SRITAMIN, MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Development Population of Root-Knot Nematode (Meloidogyne spp.) and The Level Of Damage to Some Plants Solanaceae Family This research started from November 2018 until March 2019 in the  experimental garden Pegok Faculty of Agriculture, University Udayana. It uses a complete randomized design with 4 treatments and 6 repeats. The study treatment uses some of the Solanaceae family plants such us tomato (Lycopersicon esculentum), eggplants (Solanum melongena L), large red chili pepper (Capsicum annum), cayenne pepper (Capsicum frutescens), which was given 500 of nematodes Meloidogyne spp. on Each polybag. The observed parameters include the development of the population of nematode Meloidogyne spp. for 2 life cycles in 1 gram of root and 300 grams of soil and measuring the rate of crop damage. Nematodes Meloidogyne spp. is an important parasitic nematodes in the world. Solanaceace plants are widely cultivated in Indonesia because of their high economic value and become an important food ingredient. One of the problems in aquaculture Solanaceae is the attack nematodes Meloidogyne spp.. The highest population of the research results is in tomato plants with a damage rate of 68.3%. The lowest population amount in chili pepper plants with a damage rate of 11.7%. The less-liked plant Nematoda Meloidogyne spp. is a chili pepper so it can be used as an alternative crop rotation.